2009
DOI: 10.3844/ajassp.2009.1436.1439
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Flower Development, Chlorophyll Mutation and Alteration in Plant Morphology of Curcuma alismatifolia by Gamma Irradiation

Abstract: Problem statement: Curcuma alismatifolia Gagnep., commonly known as 'Thai tulip' or pathumma is a member of the family Zingiberaceae. This herbaceous perennial which can be grown from rhizomes have a great potential for use as a cut flower, flowering potted plant and as a garden plant for tropical landscaping. Unlike other bulbous floral crops, research on C. alismatifolia using gamma irradiation has been a least subject of investigation. Approach: Presently, the use of induced mutation in plant improvement ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 2 publications
2
24
0
Order By: Relevance
“…Plant height is a quantitative trait which is predominantly controlled by polygene. Each gene contributes small effects called genetic addictive effect [23]. In some cases mutation are not stable, they will undergo recombination during meiosis [24].…”
Section: Resultsmentioning
confidence: 99%
“…Plant height is a quantitative trait which is predominantly controlled by polygene. Each gene contributes small effects called genetic addictive effect [23]. In some cases mutation are not stable, they will undergo recombination during meiosis [24].…”
Section: Resultsmentioning
confidence: 99%
“…Plant associated with the biosynthesis of primary metabolic traits may have reduced. Abdullah et al, (2009) said that the increase in the plant height may be due to the reason that certain chemical mutagens produce single base substitutions with different mutation spectra; because of which broad variation occur in morphological parameters as compared to control. He also stated that plant height is quantitative trait which is predominantly controlled by polygenes.…”
Section: Vegetative Charactersmentioning
confidence: 99%
“…γ-rays reported as useful mutagens for plant mutation breeding and it was employed to develop 64% of the radiationinduced mutant varieties [9,[10][11][12][13][14][15][16]21]. Kozlowska-kalisz [22] reported that, a dose of 20 Gy inhibited growth of samples and 70 Gy was the lethal dose of PLBs of the Cymbidium orchid.…”
Section: Generation Of Variation Lines By γ-Rays Irradiationmentioning
confidence: 99%
“…The survival rate of irradiated samples was determined after cultivation of 4 months for calculating the optimal dose for radiosensitivity, i.e. LD50 (lethal dosage of 50% irradiated samples) [14,18].…”
Section: Determination Of Ld50mentioning
confidence: 99%
See 1 more Smart Citation